The Influence of Islamic Religious Education on Students' Morals Vocational School - Asep Mulyawan; Zubairi Zubairi; Nurdin Nurdin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims to determine whether Islamic religious education influences the formation of students' morals in vocational schools. This research was conducted using a research sample of 40 students. In processing the data, we carry out the following methods: Editing, namely checking the questionnaire filled out by the respondent. Scoring is giving a score according to the level. Data obtained from distributing questionnaires was processed using statistical methods. Look for correlation numbers using the data discussed between two interrelated variables. Then, the data uses the product moment correlation formula to study the hypothesis of whether or not there is an influence between the variables. Based on the results of product-moment correlation calculations, at the 5% significance level, r table = 0.312; at the 1% significance level, r table = 0.403. This means that there is a significant positive correlation at the 5% significance level (0.692 > 0.312) and the 1% significance level (0.692 > 0.403). This means that the alternative hypothesis (Ha) is accepted and proven to be true because